Mid‐term results for the retroluminar transobturator sling suspension for stress urinary incontinence after prostatectomy - Bauer, Ricarda M.; Soljanik, Irina; Füllhase, Claudius; Karl, Alexander; Becker, Armin; Stief, Christian G.; Gozzi, Christian (BJU international, 2011)
Study Type – Therapy (case series)  Level of Evidence 4 What’s known on the subject? and What does the study add? Several studies showed encouraging early results of the AdVance® sling. However, mid‐term and long‐term results are missing. We were able to show that the AdVance® sling is also, in a longer follow up (median follow‐up of 27 months), an effective, safe and attractive treatment option with stable results for male SUI after radical prostatectomy. OBJECTIVE • To evaluate prospectively the efficacy of the retroluminar transobturator male sling (AdVance® sling) for the functional treatment of stress urinary incontinence (SUI) after prostatectomy. PATIENTS AND METHODS • A total of 137 patients with grade II–IV SUI, resulting from radical prostatectomy, were treated with the AdVance® sling in a prospective clinical study. In all, 11 patients were lost to follow‐up. A total of 17 patients (13.5%) had additional adjuvant radiotherapy before sling implantation. • Before and after sling implantation, a standardized 1‐h pad test was performed and post‐void residual urine, uroflowmetry, quality‐of‐life scores and the International Index of Erectile Function (IIEF‐5) were assessed. • When calculating the cure and improvement rates, ‘cure’ was defined as no pad use or one dry prophylactic pad; and ‘improved’ was defined as 1–2 pads or reduction of pads ≥50%. RESULTS • After a median (range) follow‐up of 27 (20–37) months, and a mean follow‐up of 27.2 months, the success rate was 75.4% with 51.6%‘cured’ and 23.8%‘improved’. • Overall daily pad use, urine loss in the 1‐h pad test and quality‐of‐life scores improved significantly after sling implantation. • Compared with 1‐year follow‐up data, no worsening over time was noticed and no additional complications were seen. CONCLUSION • With a mid‐term follow‐up, the retroluminar transobturator male sling is an effective, safe and attractive treatment option for SUI after radical prostatectomy. Results are stable over time.